Analisis Biaya Pemasaran dan Target Perolehan Berdasarkan Tipe Kamar Hotel Namira Syariah Surabaya - Winda Wulandari; Syamsul Arifin (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study aims to analyse marketing costs and revenue targets based on room types at Hotel Namira Syariah Surabaya. The hotel adopts a Sharia concept, prioritising Islamic principles in its services, facilities, and daily operations. The research employs a qualitative method with a case study approach to gain a comprehensive understanding of the hotel’s marketing strategies. Data were collected through direct interviews with hotel management, Front Office staff, and Financial Administration personnel. The findings reveal that the allocation of marketing costs at Hotel Namira Syariah Surabaya is tailored to the types of rooms offered. The primary marketing strategy employed is digital marketing, encompassing the use of social media, search engine optimisation (SEO), and partnerships with online reservation platforms. Additionally, traditional marketing methods, such as pamphlets and brochures, are still utilised to complement digital strategies. The Suite Room type and the Sakinah Wedding package are marketed towards the upper-class customer segment seeking comfort and exclusive experiences. Conversely, the Superior Room and Deluxe Room types target business travellers, families, and customers seeking comfortable yet affordable accommodation. The revenue target analysis indicates that variations in room types significantly contribute to the hotel’s income. For instance, the Suite Room, catering to the premium segment, commands a higher price point and thus achieves higher revenue targets. Efficient management of marketing costs and an accurate market segmentation approach have proven instrumental in helping the hotel achieve its revenue objectives. This research provides strategic insights for hotel management to devise more effective marketing strategies and maximise revenue. Furthermore, it highlights the importance of cost analysis and market segmentation in supporting the sustainability of Sharia-based hotels amidst the competitive hospitality industry.